Formation and Regulation of Mitochondrial Membranes - Laila Cigana Schenkel; Marica Bakovic (International Journal of Cell Biology)
Mitochondrial membrane phospholipids are essential for the mitochondrial architecture, the activity of respiratory proteins, and the transport of proteins into the mitochondria. The accumulation of phospholipids within mitochondria depends on a coordinate synthesis, degradation, and trafficking of phospholipids between the endoplasmic reticulum (ER) and mitochondria as well as intramitochondrial lipid trafficking. Several studies highlight the contribution of dietary fatty acids to the remodeling of phospholipids and mitochondrial membrane homeostasis. Understanding the role of phospholipids in the mitochondrial membrane and their metabolism will shed light on the molecular mechanisms involved in the regulation of mitochondrial function and in the mitochondrial-related diseases.